Pengaruh Pelatihan Tenaga Kesehatan terhadap Akurasi Rekam Medis Elektronik di Klinik Liza Medika Kota Jambi - Liza Ninda; Endang Komara; Rinawati Rinawati (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
The implementation of electronic medical records (EMR) is an important part of the digital transformation of healthcare services, but in practice there are still problems related to the accuracy of data entry by healthcare workers. Inaccurate and incomplete EMR records have the potential to reduce service quality, patient safety, and clinic accountability. This study aims to analyze the influence of knowledge, skills, ethical understanding, and training frequency on the accuracy of electronic medical record completion at the Liza Medika Clinic in Jambi. This study uses a quantitative approach with an analytical design, involving healthcare workers as respondents. Data collection was conducted through a structured questionnaire, while data analysis used linear regression tests to assess the partial and simultaneous effects between variables. The results showed that knowledge, skills, ethical understanding, and training frequency had a significant effect on the accuracy of EMR completion, both partially and simultaneously. These findings indicate that the accuracy of EMR recording is influenced by the comprehensive competence of health workers. Therefore, this study recommends strengthening competence through continuous training, improving technical skills, and professional ethics coaching as strategies for improving the quality of electronic medical record documentation.